Internet Banking Acceptance: A Comparative Study Between the Kingdom of Saudi Arabia and the USA - Ezzi, Shaza W (Archives of Business Research, 2015)
Internet banking, as with various types of electronic commerce, has grown from consumers’ needs to have greater access to banking services beyond the normal operating hours of teller-staffed banks. Also, new applications such as mobile devices used for Internet banking have provided the impetus to meet rapidly growing and sustained increases in retail e-commerce. Internet banking (IB) has been well-researched from the perspectives of perceived ease of use (PEOU) and perceived usefulness (PU) as indicants that positively affect adoption. Using the Consumer Internet Banking Model (CIBM) the goal in the present study was to investigate IB adoption based on the effects of three additional factors: perceived privacy, perceived Web security, and trust. The CIBM is a theoretical model designed to help researchers and practitioners to better understand the acceptance and adoption of Internet Banking. The initial findings of the present study suggest that Saudi Arabian respondents differ significantly from their USA/American counterparts with respect to security, privacy, and trust with respect to adoption of Internet banking, and intentions to use Internet banking. The final section of the paper presents future research avenues and concluding remarks of the findings. Keywords: Internet banking, Perceived Privacy and Perceived Web Security, Trust, Saudi Arabia, USA